#TITLE_ALTERNATIVE# - (NIM : 20512053) ; Pembimbing Dr. Bambang Prijamboedi, KARNELASATRI
Electronic structure from materials very important to predict its physical and chemical properties. Electronic structure information from the ground state and exitation state are needed for accurate prediction. Electronic structure calculation with Density Functional Theory (DFT) has been carried out to predict ground state in various experiments, meanwhile the calculation method based on Time-dependent Density Functional Theory (TD-DFT) for excitation state is rarely reported. The aim of this research is to study electronic structure from ZnO at ground state with exchange-correlation GGA-PBEsol and excitation state by TDDFT with FP-LAPW (Full-Potential Linearized Augmented-Plane Wave) method and exchange-correlation RPA (Random Phase Approximation) which is implemented in exciting-code software. The results were DOS (Density of State), band structure, loss function, and evolution q-depend loss function. Valence band mostly derived from O p and Zn d while conduction band derived from Zn s and O p character contribution. Direct band gap of ZnO single cell is 0.70 eV, while indirect band gap of ZnO supercell is 1,91 eV. Furthermore, loss function data in range 0-15 eV ZnO single cell showed nine peaks at 1.09; 1.63; 2.50; 3.37; 4.24; 7.51; 11.10; 11.54 and 13.28 eV. Momentum dependent loss function showed the decreasing of peak intensity with the increasing of momentum on energy peaks of 1.09; 1.63; 2.50 and 4.24 eV, meanwhile peaks of 3.37; 7.51; 11.10; 11.54 and 13.28 eV increase with the increasing momentum. Loss function of ZnO supercell with oxigen vacancy at 3,125% in the range at 0-13 eV showed eleven peaks at 2.06; 2.36; 2.69; 2.99; 3.32; 3.98; 5.96; 7.12; 8.44; 9.01 and 11.82 eV. Meanwhile q-dependent loss function showed the decreasing peaks intensity with the increasing momentum on peaks at 2.06; 2.69; 2.99 and 3.32 eV, peaks at 2.36 and 11.82 eV showed increasing peaks, while peaks at energy of 5.96; 7.12; 8.44 and 9.01 eV did not show significant changes. From the comparison of the amount of the loss function spectra of ZnO single cell and ZnO supercell, it can be concluded that the defects caused the oxygen vacancies in ZnO supercell increase the amount of spectrum loss function that appears.